2003
DOI: 10.1207/153276503321828022
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Participation: Evaluation of a Health Promotion Program for Low Income Seniors

Abstract: This article describes a qualitative evaluation of the Seniors Active Living in Vulnerable Elders (ALIVE) program, a 10-month health promotion program for low income seniors. Program interventions delivered in seniors' apartment buildings included exercise classes, health information sessions (i.e., health corners), and newsletters. The evaluation examined program participation, program impacts, and how the program worked. The most frequent reason for joining the program was recognizing the benefits of exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Four studies included interventions delivered by peers [ 77 80 ], eight were led by the study participants themselves [ 65 , 76 , 81 86 ], one involved both professionals and students [ 87 ], four were led by study participants with some support from help desk and community centres [ 67 , 88 90 ] and 19 studies were led by professionals [ 66 , 69 75 , 91 – 103 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies included interventions delivered by peers [ 77 80 ], eight were led by the study participants themselves [ 65 , 76 , 81 86 ], one involved both professionals and students [ 87 ], four were led by study participants with some support from help desk and community centres [ 67 , 88 90 ] and 19 studies were led by professionals [ 66 , 69 75 , 91 – 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 12 studies were rated as high and medium-high RoB [ 65 , 69 , 70 , 72 – 74 , 76 , 78 , 85 , 95 , 103 , 104 ], 12 studies as moderate RoB [ 70 , 71 , 75 , 80 , 83 , 84 , 93 , 94 , 97 , 98 , 100 , 102 ] and 21 as low or low-moderate RoB [ 66 68 , 77 , 79 , 81 , 82 , 86 , 87 , 89 , 90 , 92 , 96 , 98 100 , 105 – 107 ]. The main RoB issues with these studies included small sample size, poor selection of participants and differences observed between intervention and control group participants at baseline.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research exploring this topic has found that while older adults value social interactions with their peers, they may not be concerned with having developing long-term relationships, and these relationships are easily terminated if the relationship is not reciprocated [ 27 ]. Similarly, Buijs et al [ 28 ], found that conflict between building residents prevented some residents from attending a health promotion program. Relocation in later life, such as to a seniors’ building or assisted-living facility, may also make establishing new relationships for older adults difficult due to worsening health or a decline in physical or cognitive functioning [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%